Teaching with technology and higher education: a brave new world?. Issue 1 (2nd January 2019) - Ingleby, Ewan; Wilford, Barbara; Hedges, Clive
ABSTRACT: This paper explores the application of technology to pedagogy in higher education. The data are gathered from 21 academics who apply technology to their teaching with University students in England. The research is based on a qualitative inductive methodology. The findings reveal that a complex range of personal, social and professional factors influence pedagogy with technology in higher education. The paper makes an original contribution to knowledge by outlining some of the challenges that exist in using technology to teach in higher education. The research participants do not think that applying technology to teaching is necessarily representative of best pedagogical practice. Caution and thought are recommended if pedagogy with technology in higher education is to be developed effectively. The research reveals that transformative pedagogy is possible when technology is applied to teaching in higher education; however, this necessitates considering the needs of the students alongside reflecting on the personal, social and professional backgrounds of those who are teaching in higher education. This innovative approach to professional development with technology is developed in the paper.